Performance comparison of machine learning and GPU accelerated solvers in high-fidelity simulation of Cambridge stratified flames - Min Zhang; Guanlin Dang; Runze Mao; Yuqing Cai; Ruixing Yang; Han Li; Zhi X. Chen (Fuel, 2026)

Divergent drivers of cropland soil organic carbon under intensive cultivation and cropland protection contexts in Northeast China - Qixing Yao; Zhichao Li; Xiaoming Wan; Ruixing Hou; Xiaoxu Jia; Bayier Wulijia; Hongxi Ma; Xiaoyong Liao (Soil and Tillage Research, 2026)

Cadmium in global topsoil: Spatial distribution, associated factors, and cropland exposure screening - Ruixing Huang; Zhentao Xiao; Chengxue Ma; Jun Ma; Jie Li; Qiang He; Xiaoliu Huangfu (Journal of Hazardous Materials, 2026)

Effects of structural heterogeneity in soil humic acids from distinct river basins on Tl(III) binding-reduction: Kinetics and mechanisms - Hongye Li; Die Hu; Chengxue Ma; Ruixing Huang; Yuheng Huang; Qiang He; Hongxia Liu; Xiaoliu Huangfu (Journal of Hazardous Materials, 2026)

A domain-enhanced multi-agent framework for trustworthy literature screening in water research - Runzhi Wang; Xinlu Lin; Baoyi Zhong; Jiaxuan Li; Ruixing Huang; Yu Huang; Yajuan Cai; Chotiwat Jantarakasem; Yang Xiang; Konstantinos Plakas; Jun Ma; Yumeng Zhao (Water Research, 2026)

Eco-friendly plant-enzyme-induced mineralization coatings for corrosion protection of low-carbon steel - Xuanhua Feng; Jiayi Li; Yuxuan Zou; Yiran Gao; Jie Wei; Cheng Wang; Ruixing Wang (Journal of Cleaner Production, 2026)

Design of functional hydrogel beads based on polysaccharide-encapsulated Ganoderma lucidum spores for stability and targeted gastrointestinal delivery of protein–spore complex - Longqin Li; Ang Ma; Jiang Ni; Ruixing Chen; Junzhe Zhang; Zipeng Gong; Hai-Ning Lyu (Carbohydrate Polymers, 2026)

Eco-friendly flotation separation of molybdenite from chalcopyrite using thiotriazinone as a novel selective depressant - Mengyang Li; Xiao Wei; Ruixing Fu; Hao Lai; Shaojun Bai; Peilun Shen; Dianwen Liu; Jian Liu (Journal of Environmental Chemical Engineering, 2026)

No-tillage practices mitigate warming-induced yield losses in wheat by enhancing source-sink coordination - Yibo Li; Fulu Tao; Ruixing Hou; Senthold Asseng; Matthew Reynolds (Field Crops Research, 2026)

Reductive transformation of aqueous Tl(III) at the pyrite-water interface: Reactive site dynamics-controlled kinetics and electron transfer mechanisms - Chengxue Ma; Hongye Li; Ruixing Huang; Xiaoliu Huangfu; Nanqi Ren; Jun Ma (Journal of Hazardous Materials, 2026)

Evaluating degradation efficiency of pesticides by persulfate, Fenton, and ozonation oxidation processes with machine learning - Jingrui Wang; Xiaoliu Huangfu; Ruixing Huang; Youheng Liang; Sisi Wu; Hongxia Liu; Bartłomiej Witkowski; Tomasz Gierczak; Shuo Li (Environmental Research, 2025)

Nano silicon causes a shift in rhizospheric soil microbial community structure and improves nutrient uptake and assimilation in tomato plants under low temperature - Yu Shi; Lu An; Shuxun Guo; Jieyu Li; Huixian Sun; Ruixing Zhang; Hailiang Zhao; Longqiang Bai; Leiping Hou; Yi Zhang; Golam Jalal Ahammed (Soil and Tillage Research, 2025)

Room temperature synthesis of one-dimensional hierarchical hollow BiOBr with tunable photocatalysis reaction pathway for RhB under visible light - Niya Yang; Ruixing Li; Yajuan Xu; Min He; Daiwei Li; Suisui Su; Jiao zhang; Cuiqing Zhang; Jia Dong; Siqi Ying; Shizheng Zheng; Changyuan Hu (Environmental Research, 2025)

Optimizing Strategy for Whole-Genome Genotype Imputation in Scallops - Yujue Wang; Ruixing Yao; Liang Zhao; Qianqian Zhang; Moli Li; Xiangfu Kong; Pingping Liu; Shanhuan Huang; Chen Hu; Zhenmin Bao; Xiaoli Hu (Aquaculture, 2025)

Identification and characterization of Pantoea eucalypti as the causative agent of soft rot disease in Chinese chive (Allium tuberosum Rottler ex Sprengle) in China☆ - Fengwei Li; Zhenyu Zhong; Ruixing Wang; Xiaofeng Zhang; Fuyou Li; Guanhua Ma; Xiaozhou Ma; Xianchao Sun (Physiological and Molecular Plant Pathology, 2024)

Photochemical transformation and immobilization of thallium in the presence of iron and arsenic: Mechanistic insights from the coupled formation of arsenate complexes - Chengxue Ma; Hongye Li; Xiaoliu Huangfu; Ruixing Huang; Jun Ma (Journal of Hazardous Materials, 2024)

Linkages of soil and microbial stoichiometry to crop nitrogen use efficiency: Evidence from a long-term nitrogen addition experiment - Huarui Gong; Jing Li; Zhen Liu; Ruixing Hou; Yitao Zhang; Yan Xu; Wanxue Zhu; Linsheng Yang; Zhu Ouyang (CATENA, 2024)

Characterization of a Homeodomain-Leucine Zipper Gene 12: Gene Silencing in Pepper and Arabidopsis-Based Overexpression During Abiotic Stress - Ruixing Zhang; Quanhui Li; Jingjing Xiao; Saeed ul Haq; Abid Khan; Guoxin Cheng; Huiling Yan; Zhenhui Gong (Journal of Plant Growth Regulation, 2024)

The contribution and flow of microbial residual carbon in soil aggregates following forest restoration on the Loess Plateau, China - Yulin Liu; Ruixing Zhang; Xiaozhen Wang; Jiwei Li; Zhouping Shangguan; Lei Deng (CATENA, 2024)

Combined toxicity of biochar with nanoplastics or silver nanoparticles toward Chlorella vulgaris - Hongye Li; Xiaojun Zhou; Ruixing Huang; Qiang He; Zhengsong Wu; Yuheng Huang; Zhiheng Li; Yu Liu; Xiaoliu Huangfu (Algal Research, 2024)

Effects of long-term blue light irradiation on carotenoid biosynthesis and antioxidant activities in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Ruixing Zhang; Wenjing Yang; Qiming Pan; Qi Zeng; Chengtai Yan; Xue Bai; Yao Liu; Lugang Zhang; Baohua Li (Food Research International, 2023)

The effects of short term blue light treatment on promoting nutrition value in Chinese cabbage - Ruixing Zhang; Yulin Liu; Qiming Pan; Abid Khan; Xue Bai; Muhammad Ali; Wenjing Yang; Lugang Zhang; Baohua Li (Food Chemistry, 2023)

Transcriptome and network analyses reveal key pathways and genes involved in response to carotenoid deposition in scallop muscle - Tingting Li; Yihan Zhang; Shiqi Liu; Moli Li; Ruixing Yao; Senyu Niu; Jingyao Yuan; Huizhen Wang; Jingjie Hu; Zhenmin Bao; Xiaoli Hu (Frontiers in Marine Science, 2023)
Carotenoids are essential nutrients for humans and animals, and carotenoid content has become an important trait to evaluate the nutritional value of many cultured animals. Marine animals provide humans with diverse carotenoids, and developing carotenoid-enriched varieties has been the focus of marine animal breeding. Understanding the molecular mechanism of carotenoid deposition could benefit marine animal breeding for carotenoid content improvement. In the present study, transcriptomic analysis of adductor muscle was performed between Yesso scallop ( Patinopecten yessoensis ) with white muscle (WM) and carotenoid-enriched orange muscle (OM). A total of 683 differentially expressed genes (DEGs) were identified, with 302 and 381 genes being up- and down-regulated in OM scallop. Gene co-expression network analysis identified four carotenoid accumulation−related modules, including three up-regulated modules and one down-regulated module. The genes in up-regulated modules mainly participate in the pathways of translation and transcription (MEgreen), immune system (MElightyellow), and lipid metabolism (MEpink), while the down-regulated module is mainly enriched with genes involved in various metabolic pathways (MEturquoise). As the causal gene responsible for muscle coloration in scallop, PyBCO-like 1 is the hub gene of MEturquoise and showed strong connectivity with NR2F1A , a transcriptional factor involved in the regulation of retinoic acid. In addition, the up-regulated DEGs, including WDR3 , RPP29 , TBL3 , RIOK2 , and NOB1 from “ribosome biogenesis”, HSP70 s and HSP702B s from “antigen processing and presentation”, and ACOX1 from “PPAR signaling pathway” were identified as hub genes, indicating the potential regulatory role of these genes and pathways in response to carotenoid accumulation. Our data contribute to a deeper understanding of the regulatory and response mechanisms of carotenoid accumulation in marine animals.

Exploring the mechanism of Chaihujia Longgu Muli decoction in the treatment of epilepsy in rats based on the RhoA/ROCK signaling pathway - Gang Feng; Xianghua Liu; Baoying Wang; Ruixing Li; Yaxin Chang; Nannan Guo; Yawei Li; Tiantian Chen; Bingxiang Ma (Molecular Biology Reports, 2023)

GhMYC2 activates cytochrome P450 gene CYP71BE79 to regulate gossypol biosynthesis in cotton - Xinpei Han; Yadi Xing; Yaqian Zhu; Lei Luo; Lulu Liu; Yaohua Zhai; Wenjing Wang; Ruixing Shao; Maozhi Ren; Fuguang Li; Qinghua Yang (Planta, 2022)

Organic fertilizer amendment promotes wheat resistance to herbivory and biocontrol services via bottom-up effects in agroecosystems - Shimin Gu; Myron P. Zalucki; Xingyuan Men; Jing Li; Ruixing Hou; Qingqing Zhang; Feng Ge; Fang Ouyang (Journal of Pest Science, 2022)

An Automated Approach to Coastline Simplification for Maritime Structures with Collapse Operation - Jiawei Du; Fang Wu; Ruixing Xing; Jinghan Li; Xianyong Gong (Marine Geodesy, 2021)

New 1, 2-naphthoquinone-derived pigments from the mycobiont of lichen Trypethelium eluteriae Sprengel - Buddha Bahadur Basnet; Li Liu; Wen Zhao; Ruixing Liu; Ke Ma; Li Bao; Jinwei Ren; Xinli Wei; Haiyang Yu; Jiangchun Wei; Hongwei Liu (Natural Product Research, 2019)

Depth Contour Smoothing Based on the Fitting of Multi-Segment Bezier Curves - Jinghan Li; Fang Wu; Xianyong Gong; Jiawei Du; Ruixing Xing (Marine Geodesy, 2018)

Analysis of chloroplast differences in leaves of rice isonuclear alloplasmic lines - Danfeng Tang; Fan Wei; Muhammad Haneef Kashif; Aziz Khan; Zengqiang Li; Qiqi Shi; Ruixing Jia; Hongying Xie; Li Zhang; Bin Li; Peng Chen; Ruiyang Zhou (Protoplasma, 2018)

Changes and controlling factors of cropland soil organic carbon in North China Plain over a 30-year period - Daorui Han; Zhigang Sun; Fadong Li; Ruixing Hou; Jing Li; Zhu Ouyang; Binbin Li; Changwei Cao (Plant and Soil, 2016)

Autophagy Regulates Vascular Endothelial Cell eNOS and ET-1 Expression Induced by Laminar Shear Stress in an Ex Vivo Perfused System - Fengxia Guo; Xiaohong Li; Juan Peng; Yaling Tang; Qin Yang; Lushan Liu; Zuo Wang; Zhisheng Jiang; Ming Xiao; Chuyu Ni; Ruixing Chen; Dangheng Wei; et al. (Annals of Biomedical Engineering, 2014)

A laboratory investigation of microbe-inducing CdCO3 precipitate treatment in Cd2+ contaminated soil - Li Li; Chunxiang Qian; Liang Cheng; Ruixing Wang (Journal of Soils and Sediments, 2010)